Evaluation of patient awareness of 4v and 9v HPV vaccines: A Turkish survey : Patient awareness of 4v and 9v HPV vaccines - Akcaoglu , Tugba; Ucar , Elif; Dogan , Ozan (Journal of Surgery and Medicine, 2024)
Background/Aim: The 9-valent (9v) Human Papillomavirus (HPV) vaccine was implemented in Turkey in December 2022 and has just started to be applied. The vaccine is intended to protect against diseases caused by Human Papillomavirus (HPV) Types 6, 11, 16, 18, 31, 33, 45, 52, and 58. Awareness of vaccines in Turkey can be improved through physicians’ and health workers’ efforts, social media and other communication channels. Methods: To guide awareness-raising efforts pertaining to vaccines, we asked our patients who applied for the HPV vaccine at the beginning of 2023 to answer a questionnaire. The survey was prepared to reflect vaccine-related awareness levels of patients applying for the 4v and 9v HPV vaccines. Results: It is noteworthy that the monthly income of patients applying for the vaccine was below the national average. Doubts about the effectiveness of the vaccine and levels of anxiety about its side effects are still high. Less than half of individuals who applied for vaccination received gynecological exams and regular Pap smears. Patients were largely unaware that there were different vaccines against HPV, that the 9v HPV vaccine provides better protection than the 4v HPV vaccine, and that everyone, both male and female, can be vaccinated and can benefit from HPV vaccines. Conclusion: Our findings revealed the social aspects involved in raising levels of vaccine awareness throughout Turkey. Overall, people still have doubts and concerns about HPV vaccination, and they are clearly worried about side effects. Physicians can take these concerns into consideration while providing clinical counseling in order to inhibit the spread of disease.